IMPLEMENTASI EKSTRAKULIKULER BADAN DAKWAH ISLAM DI SMA NEGERI 5 MALANG - Khoridatul Masruroh; Muhammad Sulistiono; Arief Ardiansyah (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Islamic Da'wah Agency (BDI) is an organization under the auspices of the IntraSchool Student Organization (OSIS) in which there are also several extra-religious activities whose role is to instill religious values in students in schools that include intellectual, social, and artistic fields. This research was conducted in SMA Negeri 5 Malang. This research uses a case study approach. Data collection methods used were participant observation, semi-structured interviews, and documentation . data analysis techniques using data condensation, data presentation, Conclution drawing or verification and presented descriptively. Extracurricular Islamic Da'wah Agency is an organization in the religious field under the auspices of the Intra-School Student Organization with the background of strengthening school religious activities and accommodating the interests and talents of students. as for the planned program of activities that have been developed, namely; congregational worship at school, blessing Friday, maintaining mosques, routine studies, natural tadabur, Islamic arts, social services, meetings of the Islamic Da'wah Agency in Malang, and the Commemoration of Islamic Holidays. the implementation of the program of activities there are daily, weekly and incidental. As for the success in implementing the Islamic Da'wah Agency's extracurricular activity program, namely as one of the locomotives in religious activities, there has been a change in student discipline.